Evaluación general del sistema de agua potable y aspectos básicos de saneamiento de la ASADA Agrimaga, ubicada en el cantón de Guácimo, en Limón, influenciado por el Acuífero Guácimo-Pococí. - Sánchez-Murillo, Geisel (Instituto Tecnológico de Costa Rica, 2018)
Within the framework of the project "Strengthening water management in rural aqueducts in the areas of influence and connectivity of the Aquifers of Guácimo-Pococí, Prioritized Area Tortuguero", the ASADA of Agrimaga, Puente Negro and Milla Tres, is chosen for perform a general evaluation of the community aqueduct system, where the capacities in the subject of water quality monitoring are observed, in the internal administrative management, the lack of assertive and effective communication to and from the users of the water service and the challenges to create working plans in the short, medium and long term. This panorama resulted in different diagnostic tools such as questionnaires, interviews, field observations, application of institutional instructions, as well as the implementation of the Self-evaluation Guide for the Improvement and Efficiency Plan; determined the need to conduct a series of technical training, financial measures, safety measures and water management, adjusted to the needs of the actors of the aqueduct, from the Board of Directors, to community leaders, youth and children of environmental education and management of the water in the community. The Association of ASADAS, was another determining factor that needs to improve its management, sharing experiences and support of other aqueducts in the area. With respect to the management tool designed for the ASADA, after an analysis of priorities, resources and initial diagnoses, it had been decided to build a plan of operation and maintenance of the system. As well as the recommendation to train the plumber as soon as possible in the topics of monitoring and control of water quality.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2018.
Keywords: ASADAS; Agua; Fuentes; Monitoreo; Gestión